2013
DOI: 10.1158/0008-5472.can-12-3767
|View full text |Cite
|
Sign up to set email alerts
|

FOXO3a Is a Major Target of Inactivation by PI3K/AKT Signaling in Aggressive Neuroblastoma

Abstract: Neuroblastoma is a pediatric tumor of the peripheral sympathetic nervous system with a highly variable prognosis. Activation of the phosphoinositide 3-kinase (PI3K)/AKT pathway in neuroblastoma is correlated with poor patient prognosis, but the precise downstream effectors mediating this effect have not been determined. Here we identify the forkhead transcription factor FOXO3a as a key target of the PI3K/AKT pathway in neuroblastoma. FOXO3a expression was elevated in low-stage neuroblastoma tumors and normal e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(111 citation statements)
references
References 44 publications
3
106
1
Order By: Relevance
“…Somatic deletion of all three FOXOs (FOXO1, FOXO3, and FOXO4) engenders a cancer-prone condition in mice, further strengthening its tumor suppressor role in vivo (Paik et al 2007). Consistent with this, decreased expression of FOXO3a associated with poor outcomes in breast cancer and neuroblastoma (Sunayama et al 2011;Jiang et al 2013;Santo et al 2013). Conversely, FOXO3a nuclear localization is associated with good prognosis in luminal-like breast cancer (Habashy et al 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Somatic deletion of all three FOXOs (FOXO1, FOXO3, and FOXO4) engenders a cancer-prone condition in mice, further strengthening its tumor suppressor role in vivo (Paik et al 2007). Consistent with this, decreased expression of FOXO3a associated with poor outcomes in breast cancer and neuroblastoma (Sunayama et al 2011;Jiang et al 2013;Santo et al 2013). Conversely, FOXO3a nuclear localization is associated with good prognosis in luminal-like breast cancer (Habashy et al 2011).…”
Section: Discussionsupporting
confidence: 53%
“…Further evidence was provided for this regulation, including the finding that mutant ALK likely controls RET expression levels through FOXO3a signaling. The FOXO3a forkhead transcription factor was previously shown as a key target of the PI3K/AKT pathway in neuroblastoma and essential for their survival (26). Here, we showed that mutant ALK signaling blocks FOXO3a phosphorylation through PI3K/AKT and that FOXO3a regulates RET expression, thus strongly indicating the existence of a mutant ALK-PI3K/ AKT-FOXO3a-RET signaling axis in neuroblastoma cells.…”
Section: V600esupporting
confidence: 50%
“…Given the previously described regulation of FOXO3a by PI3K/ AKT signaling (26) and the observation that the related FOXO1 controls RET expression in mouse spermatogonial stem cells (39), we tested the possibility that FOXO3a could regulate RET under the control of mutant ALK. Pharmacologic inhibition of mutant ALK using LDK-378 clearly leads to the expected loss of FOXO3a phosphorylation (leading to activation of FOXO3a; Supplementary Figure S15B).…”
Section: F1174lmentioning
confidence: 99%
See 1 more Smart Citation
“…The E3 ligase, S-phase kinase associated protein 2 (Skp2), suppresses FOXO1 transactivation, and eliminates its effect on inhibition of cell proliferation. The normal function of Skp2 phosphorylates the Ser256 site of FOXO1, and subsequently, causes degradation of FOXO1 via the proteasomal pathway (29).…”
Section: Phosphorylation Of Foxo Proteinsmentioning
confidence: 99%